Is Decentralisation Compatible with the Application of Performance Management? The Impacts of Minimum Service Standards on the Motivation of Local Government to Improve Service Delivery in the Indonesian Decentralised System - Mohammad Roudo; Adrian Campbell; Simon Delay (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. The extent to which decentralisation is compatible with effective performance management that is able to influence the motivation of public sector bodies has been a subject of limited attention in the academic literature. This paper contributes to that limited debate by investigating the extent to which minimum service standards (MSS), a performance management tool directed at local government service delivery, influences the motivation of local governments in highly decentralised systems, such as that in Indonesia. The two research questions are: (a) what influence does MSS have on the motivation of local governments to improve their service delivery performance, and (b) to what extent does decentralisation influence the implementation of performance management. The information used to answer these questions is taken from semi-structured interviews with eighty-three respondents from central government, district and city governments, and the non-governmental sector. The results of this study show that MSS, with its characteristic minimum thresholds, can lead to different patterns of motivation in local governments to improve service delivery. However, MSS only motivates better performance amongst those local governments whose current performance falls just below the required standard. It does not appear to motivate those who are well above or well below the standards. This study also showed the limitations of centrally led performance management systems like MSS to improve performance. They are constrained by the decentralised nature of the system, wherein the autonomy of local governments has to be respected. This implies that decentralisation is, to some extent, not compatible with effective performance management and attempts to improve local service delivery, which requires strong enforcement and effective incentives. However, this does not mean that MSS has no impact at all. Although the impact is limited, MSS, to an extent, helps to improve central-local dialogue in service delivery. This could be a good starting point for the improvement of public services in districts and cities in the future.Keywords. Minimum service standards (MSS), decentralisation, performance management, public services, local government.Abstrak. Sejauh mana desentralisasi kompatibel dengan manajemen kinerja yang efektif dapat mempengaruhi motivasi badan-badan sektor publik telah menjadi subyek perhatian yang terbatas dalam literatur akademik. Makalah ini berkontribusi pada perdebatan terbatas tersebut dengan menyelidiki sejauh mana standar pelayanan minimum (SPM), suatu alat manajemen kinerja yang diarahkan pada penyampaian layanan pemerintah daerah, mempengaruhi motivasi pemerintah daerah dalam sistem yang sangat terdesentralisasi, seperti di Indonesia. Dua pertanyaan penelitian mencakup: (a) pengaruh apa yang dimiliki SPM terhadap motivasi pemerintah daerah untuk meningkatkan kinerja penyampaian layanan mereka, dan (b) sejauh mana desentralisasi mempengaruhi pelaksanaan manajemen kinerja. Informasi yang digunakan untuk menjawab pertanyaan-pertanyaan ini diambil dari wawancara semi-terstruktur dengan delapan puluh tiga responden dari pemerintah pusat, kabupaten dan kota, dan sektor non-pemerintah. Hasil penelitian ini menunjukkan bahwa SPM, dengan batas minimum karakteristiknya, dapat menyebabkan pola motivasi yang berbeda di pemerintah daerah untuk meningkatkan penyediaan layanan. Namun, SPM hanya memotivasi kinerja yang lebih baik di antara pemerintah daerah yang kinerjanya saat ini berada di bawah standar yang dipersyaratkan. Tampaknya SPM tidak memotivasi mereka yang jauh di atas atau jauh di bawah standar. Penelitian ini juga menunjukkan keterbatasan sistem manajemen kinerja terpusat seperti SPM untuk meningkatkan kinerja. Mereka dibatasi oleh sifat sistem yang terdesentralisasi, di mana otonomi pemerintah lokal harus dihormati. Ini menunjukkan bahwa desentralisasi, sampai taraf tertentu, tidak kompatibel dengan manajemen kinerja yang efektif dan upaya untuk meningkatkan penyampaian layanan lokal yang membutuhkan penegakan hukum yang kuat dan insentif yang efektif. Namun, ini tidak berarti bahwa SPM tidak berdampak sama sekali. Meskipun dampaknya terbatas, SPM, sampai taraf tertentu, membantu meningkatkan dialog pusat-lokal dalam pemberian layanan. Ini bisa menjadi titik awal yang baik untuk peningkatan pelayanan publik di kabupaten dan kota di masa depan.Kata kunci. Standar pelayanan minimum (SPM), desentralisasi, manajemen kinerja, layanan publik, pemerintah daerah.